We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
120
4
avatar+33 

Let \(k, a_2, a_3 \) and \( k, b_2, b_3\) be nonconstant geometric sequences with different common ratios. If \(a_3-b_3=2(a_2-b_2),\) then what is the sum of the common ratios of the two sequences?

 Dec 27, 2018

Best Answer 

 #2
avatar+100791 
+3

I am gong to change the sequences as follows

 

\(k,\;\;kr_1,\;\;kr_1^2 \qquad and \qquad k,\;\;kr_2,\;\;kr_2^2\\~\\ a_3-b_3\\=k(r_1)^2-k(r_2)^2\\ =k[(r_1)^2-k(r_2)^2]\\=k[(r_1)-(r_2)][(r_1)+(r_2)]\)

 

 

\(a_2-b_2\\ =kr_1-kr_2\\ =k(r_1-r_2)\)

 


\(a_3-b_3=2(a_2-b_2)\\ k[(r_1)-(r_2)][(r_1)+(r_2)]=2[k(r_1-r_2)]\\\\ (r_1)+(r_2)=2\\ \)

.
 Dec 28, 2018
 #1
avatar+33 
0

can anyone help?

 Dec 27, 2018
 #2
avatar+100791 
+3
Best Answer

I am gong to change the sequences as follows

 

\(k,\;\;kr_1,\;\;kr_1^2 \qquad and \qquad k,\;\;kr_2,\;\;kr_2^2\\~\\ a_3-b_3\\=k(r_1)^2-k(r_2)^2\\ =k[(r_1)^2-k(r_2)^2]\\=k[(r_1)-(r_2)][(r_1)+(r_2)]\)

 

 

\(a_2-b_2\\ =kr_1-kr_2\\ =k(r_1-r_2)\)

 


\(a_3-b_3=2(a_2-b_2)\\ k[(r_1)-(r_2)][(r_1)+(r_2)]=2[k(r_1-r_2)]\\\\ (r_1)+(r_2)=2\\ \)

Melody Dec 28, 2018
 #3
avatar+100473 
+1

Very nice, Melody!!!

 

cool cool cool

CPhill  Dec 28, 2018
 #4
avatar+100791 
+1

Thanks Chris :)

Melody  Dec 28, 2018

26 Online Users

avatar
avatar
avatar
avatar
avatar